X(x+11)-17(x+11)=0

Simple and best practice solution for X(x+11)-17(x+11)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(x+11)-17(x+11)=0 equation:


Simplifying
X(x + 11) + -17(x + 11) = 0

Reorder the terms:
X(11 + x) + -17(x + 11) = 0
(11 * X + x * X) + -17(x + 11) = 0
(11X + xX) + -17(x + 11) = 0

Reorder the terms:
11X + xX + -17(11 + x) = 0
11X + xX + (11 * -17 + x * -17) = 0
11X + xX + (-187 + -17x) = 0

Reorder the terms:
-187 + 11X + -17x + xX = 0

Solving
-187 + 11X + -17x + xX = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '187' to each side of the equation.
-187 + 11X + -17x + 187 + xX = 0 + 187

Reorder the terms:
-187 + 187 + 11X + -17x + xX = 0 + 187

Combine like terms: -187 + 187 = 0
0 + 11X + -17x + xX = 0 + 187
11X + -17x + xX = 0 + 187

Combine like terms: 0 + 187 = 187
11X + -17x + xX = 187

Add '17x' to each side of the equation.
11X + -17x + 17x + xX = 187 + 17x

Combine like terms: -17x + 17x = 0
11X + 0 + xX = 187 + 17x
11X + xX = 187 + 17x

Reorder the terms:
-187 + 11X + -17x + xX = 187 + 17x + -187 + -17x

Reorder the terms:
-187 + 11X + -17x + xX = 187 + -187 + 17x + -17x

Combine like terms: 187 + -187 = 0
-187 + 11X + -17x + xX = 0 + 17x + -17x
-187 + 11X + -17x + xX = 17x + -17x

Combine like terms: 17x + -17x = 0
-187 + 11X + -17x + xX = 0

The solution to this equation could not be determined.

See similar equations:

| 6t^2+6t-1=0 | | 7=-x+215 | | -3(5x+1)=6 | | 8b=-4+2(2+5b) | | R+VR=7 | | 116-x=216 | | 0.1-0.01(x+1)=-0.01(1-x) | | .04x+.07(11000-x)=660 | | y=-24-x | | 8-2(x-6)=-7x | | 6=2x+-2 | | x=2ln(6-y)+3 | | 3x+2=-20+30 | | -3(1-5r)=9+3r | | .04x+.07(1000-x)=660 | | 4b+20=60 | | F(x)=2ln(6-x)+3 | | -2m-5(1-5m)=110 | | 5+(x-9)+x=59 | | F(x)=xsq+x | | 2(x+12)+7(x-5)=4x-56 | | (8x-y-7)(6x)= | | x^3=41 | | 5y+36=10y+6 | | 0=x^3-3x-6 | | 4(2r+5)=6(r-2) | | 9-11x-7-10x=5 | | 6.1-r=3.4 | | 24d+40de= | | 4(z-3)+z=-2 | | -3(y-4)=18 | | -(9x-9)+9x= |

Equations solver categories